The book of bad things - Poblocki, Dan (Scholastic Press, 2014)
Although twelve-year-old Cassidy Bean keeps a book of bad things, she did not expect her summer with the Tremont family in rural New Jersey to be one of them--but this year Ursula, a local hoarder, has died under mysterious circumstances, and Cassidy finds that there a great many bad and dangerous things hidden in her house, including, perhaps, her vengeful ghost.